PENGARUH ASUPAN NUTRISI TERHADAP ANEMIA PADA REMAJA - Nur Oktaviana Majid; Khamidah Achyar; Kesya Ayudia Pradita; Syifa Revayanti; Rizkia Cahyaning (SINERGI : Jurnal Riset Ilmiah, 2026)
Anemia among adolescent girls remains a prevalent public health problem, with high prevalence closely associated with inadequate nutritional intake, particularly iron, protein, and vitamin C. The increased iron requirements during adolescence, driven by rapid growth and menstrual blood loss, place this group at a heightened risk of anemia when dietary intake is insufficient. This scoping review aimed to examine current scientific evidence on the impact of nutritional intake on the incidence of anemia among adolescent girls and to evaluate the effectiveness of local food–based interventions in increasing hemoglobin levels. The literature search followed the Arksey and O’Malley framework and the PRISMA-ScR guidelines, using two major databases: PubMed and Google Scholar. A total of 631 articles were identified, comprising 221 from PubMed and 410 from Google Scholar. After screening based on inclusion and exclusion criteria, seven original research articles were selected for in-depth analysis. The findings revealed four key themes: (1) low iron intake, particularly from animal sources, is the primary contributor to decreased hemoglobin levels; (2) protein and vitamin C play crucial roles in enhancing the absorption of non-heme iron; (3) irregular eating patterns, the habit of consuming tea or coffee after meals, and limited nutritional knowledge exacerbate anemia; and (4) local food–based interventions such as red spinach pudding, kelakai pudding, fish-based snacks, and combinations of boiled eggs with red guava juice were effective in increasing hemoglobin levels within 7–14 days. This scoping review underscores that anemia among adolescent girls is strongly influenced by the quality of nutritional intake and dietary habits, and it supports evidence that local foods can serve as an effective and cost-efficient approach for the prevention and management of anemia